Initial experiences of transapical beating‐heart mitral valve repair with a novel artificial chordal implantation device. Issue 5 (26th February 2022) - Wang, Shouzheng; Meng, Xu; Hu, Shengshou; Sievert, Horst; Xie, Yongquan; Hu, Xiaopeng; Sun, Yi; Luo, Zhiling; Zhou, Hongyan; Zhang, Guimin; Pan, Xiangbin
Abstract: Background: Severe mitral regurgitation (MR) is associated with progressive heart failure and impairment of survival. Degenerative MR accounts for most MV repair surgeries. Conventional mitral valve repair surgery requires cardiopulmonary bypass and is associated with significant morbidity and risks. Transapical beating‐heart mitral valve repair by artificial chordae implantation with transesophageal echocardiography (TEE) guidance has the potential to significantly reduce surgical morbidity. We report the first‐in‐human experience of degenerative MR repair using a novel artificial chordae implantation device (Mitralstitch TM system). Methods: Ten patients with severe MR underwent transapical artificial chordae implantation using MitralstitchTM system. The procedure was performed through a small left thoracotomy under general anesthesia and TEE guidance. Patients underwent transthoracic echocardiography and other assessments during the follow‐up. Results: All 10 patients with an average age of 63.7 ± 9.6 years successfully received transapical artificial chordae implantation. Their MR reduced from severe to none or trace in five patients, mild in five patients before discharge. Five patients received one artificial chordal implantation, four patients received two, and one patient received three and edge‐to‐edge repair by locking two of them. The safety and efficacy endpoint were achieved in all patients at 1‐month follow‐up. At 1‐year follow‐up, six patients had mild MR, three patients had moderate MR, one patient had recurrence of severe MR and underwent surgical repair. Conclusions: The results of this first‐in‐human study show safety and feasibility of transapical mitral valve repair using MitralStitch system. Patient selection and technical refinement are crucial to improve the outcomes.